Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1111/j.1476-5381.1985.tb17377.x
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen activates voltage‐dependent and 4‐aminopyridine sensitive K+ conductance in guinea‐pig hippocampal pyramidal cells maintained in vitro

Abstract: 1The ionic mechanism underlying the effect of (-)-baclofen in the hippocampus was investigated using guinea-pig brain slices.2 (-)-Baclofen either perfused or applied directly by microiontophoresis hyperpolarized the membrane and decreased the membrane input resistance of pyramidal cells in a dose-dependent manner.3 The value of the reversal potential for the baclofen-induced hyperpolarization, as estimated from the current-voltage relationships, was about -95 mV. 4 The reversal potential of the baclofen-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
1

Year Published

1985
1985
1993
1993

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 20 publications
9
44
1
Order By: Relevance
“…The degree of antagonism by TEA was lower than that caused by 4-AP, suggesting that 4-AP-sensitive K+ channels play a more important role than TEA-sensitive channels in baclofen antinociception. These results are in agreement with the findings of electrophysiological studies showing that 4-AP markedly antagonized or even abolished the K+ conductances induced by baclofen in neurones (Inoue et al, 1985;Stevens et al, 1985;Ogata et al, 1987), whereas TEA did not antagonize (Inoue et al, 1985) or only partially antagonized them (Stevens et al, 1985;Lacey et al, 1988). In addition, it has been shown that baclofen activates a 4-AP-sensitive K+ channel in hippocampal neurones that mediates a voltage-dependent transient outward K+ current with the characteristics of an A-current (Saint et al, 1990).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The degree of antagonism by TEA was lower than that caused by 4-AP, suggesting that 4-AP-sensitive K+ channels play a more important role than TEA-sensitive channels in baclofen antinociception. These results are in agreement with the findings of electrophysiological studies showing that 4-AP markedly antagonized or even abolished the K+ conductances induced by baclofen in neurones (Inoue et al, 1985;Stevens et al, 1985;Ogata et al, 1987), whereas TEA did not antagonize (Inoue et al, 1985) or only partially antagonized them (Stevens et al, 1985;Lacey et al, 1988). In addition, it has been shown that baclofen activates a 4-AP-sensitive K+ channel in hippocampal neurones that mediates a voltage-dependent transient outward K+ current with the characteristics of an A-current (Saint et al, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…opioid receptor agonists in neurones appear to be identical, and are insensitive to some K+ channel blockers such as tetraethylammonium (TEA) and 4-aminopyridine (4-AP) (North & Williams, 1985;Aghajanian & Wang, 1987). On the other hand, the K+ conductances elicited by GABAB receptor agonists in neurones appear to be different, as they are antagonized by 4-AP and TEA (Inoue et al, 1985;Stevens et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…(-)-Baclofen hyperpolarized the membrane, reduced the membrane input resistance and depressed the spontaneous firing. These postsynaptic actions of (-)-baclofen have been described in detail elsewhere (Inoue et al, 1985). Figure la, Figure la).…”
Section: Resultsmentioning
confidence: 53%
“…However, Newberry & Nicoll (1984b) have recently shown that (-)-baclofen exerts a prominent depressant action, which is apparently of postsynaptic nature, on rat hippocampal pyramidal cells, and have suggested the presence of postsynaptic GABAB sites in the hippocampus. This postsynaptic action of baclofen has been shown to be due to an increase in K+ conductance (Inoue et al, 1985). These findings warrant re-investigation of the reported presynaptic action of (-)-baclofen in this tissue through intracellular recordings.…”
mentioning
confidence: 54%
“…In the hippocampal slice, the (-)-baclofen-activated current is blocked by micromolar concentrations of 4-AP (Inoue et al, 1985a) whereas in the spinal cord slice concentrations of 4-AP up to 50 yM had no effect on the response to (-)-baclofen. It should, however, be noted that in hippocampal cultures the potassium current activated by (-)-baclofen was not affected by 4-AP (Brown & Gahwiler, 1987).…”
Section: Discussionmentioning
confidence: 84%